Artificial Creativity – Early Analyses of LLMs’ Creative Approaches - Pretsch, Juergen; Pretsch, Ekaterina; Fuchs, Michael (European Journal of Social Science Education and Research, 2024)
This study explores AI creativity through a two-pronged experiment: ChatGPT for language processing and MidJourney for text-to-image synthesis. Both models focused on expressing Ekman's six basic emotions. By manipulating ChatGPT's 'temperature' to vary linguistic creativity and using these outputs to guide MidJourney's image creation, the research examines the nuanced capabilities of AI in generating emotionally resonant artworks and linguistically complex prompts. The study's findings highlight two significant contributions of AI to creative domains: firstly, AI's ability to evoke specific emotions in viewers through art, effectively bridging the gap between synthetic cognition and human emotion; and secondly, AI's development of unique artistic styles, a result of assimilating and reinterpreting diverse artistic influences. These insights not only broaden our understanding of AI's creative capabilities but also point towards its potential to significantly enrich the artistic landscape.
Keywords: creativity, art, artificial intelligence (AI), human, emotions, ChatGPT, MidJourney